Tinea pedis: An Update - kumar, Vikas; Tilak, Ragini; Prakash, Pradyot; Nigam, Chaitanya; Gupta, Richa (Asian Journal of Medical Sciences, 2011)
Cutaneous fungal infections are a widespread public health concern affecting millions of people all across the world. Nearly half of those affected will experience multiple episodes of infection requiring numerous rounds of treatment. Tinea pedis is a common superficial fungal skin infection of the feet. It is emerging as an important and a significantly prevalent infection in an increasingly aging population and immunocompromised patients. This mycotic infection is contagious, frequently misdiagnosed and often inadequately treated. Considering the uprising prevalence of tinea pedis, in this review article predisposing factors, etiologic agents involved in pathogenesis, clinical presentation of the disease, proper diagnostic tests and the treatment options commercially available are reviewed. Key Words: Tinea pedis; Dermatophytes; KOH Mount; PAS Reaction DOI: http://dx.doi.org/10.3126/ajms.v2i2.4430 Asian Journal of Medical Sciences 2 (2011) 134-138